Assessment of degradation equivalent operating time for aircraft gas turbine engines - Alozie, Ogechukwu; Li, Yiguang; Diakostefanis, Michail; Wu, Xin; Shong, Xingchao; Ren, Wencheng (Cambridge University Press (CUP), 2020)
This paper presents a novel method for quantifying the effect of ambient, environmental and operating conditions on the progression of degradation in aircraft gas turbines based on the measured engine and environmental parameters. The proposed equivalent operating time (EOT) model considers the degradation modes of fouling, erosion, and blade-tip wear due to creep strain, and expresses the actual degradation rate over the engine clock time relative to a pre-defined reference condition. In this work, the effects of changing environmental and engine operating conditions on the EOT for the core engine booster compressor and the high-pressure turbine were assessed by performance simulation with an engine model. The application to a single and multiple flight scenarios showed that, compared to the actual engine clock time, the EOT provides a clear description of component degradation, prediction of remaining useful life, and sufficient margin for maintenance action to be planned and performed before functional failure.
Keywords: Equivalent Operating Time; Erosion; Creep; Degradation; Remaining useful life; Gas turbine; Fouling; Prognostics; Performance